Religious Pluralism According to K.H. Abun Bunyamin in Tafsir Al-Ma'arif - Muhamad Aroka Fadli (Aqwal: Journal of Qur'an and Hadis Studies, 2023)
The pluralism of religion in Indonesia has always been a significant topic of debate, given the diversity of this country, consisting of various ethnicities, cultures, and religions. Among the Islamic community, discussions regarding religious pluralism often become heated, with various arguments and evidence presented. One of the viewpoints that addresses religious pluralism is that of K.H. Abun Bunyamin, a prominent Islamic figure in the West Java region, as articulated in his book, Tafsir Al-Ma'arif. This research aims to understand Abun Bunyamin's perspective on religious pluralism in his work. The research method employed is a descriptive-analytical approach, involving problem description, in-depth analysis, and meticulous presentation of research findings. Data sources used include document analysis of Abun Bunyamin's writings and direct interviews with him. The research findings indicate that Abun Bunyamin vehemently rejects the idea of religious pluralism. His perspective is grounded in the interpretation of Surah Ali Imran, verse 85, in which he believes that religious pluralism is not only about recognizing the diversity of religions but also supporting the existence and diversity of these religions. Moreover, he opposes the view of proponents of religious pluralism who claim that all religions are true as long as they submit to God. Abun Bunyamin's perspective on religious pluralism is also influenced by his experiences and his position as the Chairman of the Indonesian Ulema Council (MUI) in Purwakarta Regency, as well as being a kiai who teaches the general public. This has made him more focused on strengthening faith and distancing himself from hatred towards individuals with different beliefs. Thus, this perspective reflects an effort to promote tolerance and harmony among religions in the diverse context of Indonesia.